Nutrients Return Through Leaf Litter and Their Relations with Poplar Growth Under Different Treatments of N, Irrigation and Inter-cropping - Thind, H.S.; Arora, C.L.; Toor, G.S. (Indian Journal of Agroforestry, 2020)
An investigation was planned to know the effect of nitrogen fertilization, irrigation and cropping systems on the growth of poplar trees and nutrients returned to soil through leaf litter. The treatments included two levels of irrigation (IW/PAN-E ratio of 0.5 and 1.0 during pre-monsoon season), three levels of N (0, 20 and 40 g N per tree during first two years and 0, 40 and 80 g N per tree during subsequent two years) and two cropping systems (uncropped and wheat intercropped). The results indicated that the quantity of leaf litter in various treatment combinations varied from 3.16 to 7.51 t/ha during fourth year of growth. The increase in basal area during fourth year of growth varied from 2.919 to 4.859 m2 per hectare where as the corresponding increase in tree volume varied from 31.56 to 50.00 m3 per hectare. The quantity of leaf litter in different treatments was positively linearly correlated with current annual increase in tree basal area (r = 0.67) and with current annual increment in tree volume (r = 0.74). The mean nutrient return in soil through leaf litter, irrespective of treatments, for calcium, nitrogen, potassium, magnesium, sulphur and phosphorus was 136, 56, 48, 27, 22 and 8 kg/ha, respectively. The linear correlations between increase in tree volume and nutrient return through leaf litter were significantly positive for nitrogen, phosphorus, potassium, magnesium, sulfur, iron, copper and boron.